解方程①(3x^2+x)(2x-3)-(6x-7)(x^2-4),其中x=2; ②(a-b)(a^2+ab +b^2)-b^2(b+a)-a^3,其中a=-1,b=2
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/05 04:16:12
解方程①(3x^2+x)(2x-3)-(6x-7)(x^2-4),其中x=2;②(a-b)(a^2+ab+b^2)-b^2(b+a)-a^3,其中a=-1,b=2解方程①(3x^2+x)(2x-3)-
解方程①(3x^2+x)(2x-3)-(6x-7)(x^2-4),其中x=2; ②(a-b)(a^2+ab +b^2)-b^2(b+a)-a^3,其中a=-1,b=2
解方程①(3x^2+x)(2x-3)-(6x-7)(x^2-4),其中x=2; ②(a-b)(a^2+ab +b^2)-b^2(b+a)-a^3,其中a=-1,b=2
解方程①(3x^2+x)(2x-3)-(6x-7)(x^2-4),其中x=2; ②(a-b)(a^2+ab +b^2)-b^2(b+a)-a^3,其中a=-1,b=2
①(3x²+x)(2x-3)-(6x-7)(x²-4)=6x³-9x²+2x²-3x-6x³+24x+7x²-28=21x-28
∵x=2 ∴原式=21×2-28=42-28=14
②(a-b)(a²+ab+b²)-b²(b+a)-a³=a³-b³-b³-ab²-a³=﹣2b³-ab²
∵a=-1,b=2 ∴原式=﹣2×2³-(﹣1)×2²=﹣16+4=﹣12
解方程x/(x-2)=2x/(x-3)+(1-x)/(x-5x+6)
(x^2+x)(x^2+x-3)-3(x^2+x)+8=0解方程
解方程{3X+X+2X=12}3X+X+2X=12
解方程(x-3/x)-(3-x/x+1)=5x-15/2x+2
解方程:2(X-3)(X+5)=X平方+(X+2)(X-2)+(X+7)
解方程 x(2x-4)+3x(x-1)=5x(x-3)+8
解方程 3x/x×x-1+x×x-1/3x=5/2
解方程:(x-2)(x^2-6x-9)=x(x-5)(x-3)
x/(x-2)+(x+1)/(x-6)=2x/(x-3) 解分式方程
解方程x(x-1)(x-2)(x-3)(x-4)=24x=?
解方程:x(3x-4)+2x(x+7)=5x(x-7)+90
解方程:x-2x+3x-4x+...+99x-100x=25
解方程:x-2x+3x-4x+.+99x-100x=25
解方程X(X+1)-X(X-3)=2(X+1)(X-1)+20
解方程 X(X+1)x(X+2)x(X+3)=3024
解方程|x+5|+|2x-3|
解方程2x:3=x:
解方程 |x+2|=-3x